2017
DOI: 10.3892/etm.2017.5657
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory effects of four ginsenoside monomers in humoral immunity of systemic lupus erythematosus

Abstract: Abstract. Ginsenosides Rb1, Rh1, Rg1 and Rg3 are known as the main active components extracted from the roots of the Panax ginseng C.A. Meyer, and were reported to have immunoregulatory effects. Disruption of B-cell immune regulation during the pathogenesis of systemic lupus erythematosus (SLE) may lead to the production of large amounts of antibodies. The present study investigated the effects of the four ginsenoside monomers on B-cell immune regulation and observed that they inhibited the proliferation and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…Ginsenosides Rb1, Rh1, Rg1, and Rg3 downregulated the humoral immunity related to systemic lupus erythematosus blocking B-cell secretion and proliferation. Highly pruritic chronic inflammatory disease named atopic dermatitis (AD), elevates serum IgE levels, and markedly increases levels of inflammatory cells [ 83 ]. The equipoise of Th1 and Th2 is crucial regarding the pathogenesis of AD from an immunological perspective, and controlling the delicate equilibrium among Th1, Th2, and Th17/22 and T-reg cells is crucial to the control of AD.…”
Section: Effect Of Ginseng On Autoimmune Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…Ginsenosides Rb1, Rh1, Rg1, and Rg3 downregulated the humoral immunity related to systemic lupus erythematosus blocking B-cell secretion and proliferation. Highly pruritic chronic inflammatory disease named atopic dermatitis (AD), elevates serum IgE levels, and markedly increases levels of inflammatory cells [ 83 ]. The equipoise of Th1 and Th2 is crucial regarding the pathogenesis of AD from an immunological perspective, and controlling the delicate equilibrium among Th1, Th2, and Th17/22 and T-reg cells is crucial to the control of AD.…”
Section: Effect Of Ginseng On Autoimmune Diseasementioning
confidence: 99%
“…Cho et al suggested KRG can serve preventive as well as therapeutic functions through modulating the immune network at the early stages of AD. Oral KRG has been shown to obstruct the progression of the cutaneous inflammation in an AD animal model by hindering the DCs, thymic stromal lymphopoietin, and Th2 cytokines [ 83 ].…”
Section: Effect Of Ginseng On Autoimmune Diseasementioning
confidence: 99%
“…Ginsenosides form a class of steroid glycosides and triterpene saponins. As the main active ingredients in Ginseng radix, they have various pharmacological effects, such as immunity enhancement and antiageing and antitumor effects [34][35][36]. Ginsenosides include Rb1, Rg1, Rg3, GRh2, and other monomeric saponins.…”
Section: Biomed Research Internationalmentioning
confidence: 99%
“…Mey., a valuable herb with nourishing effects and a long history of use in ancient China. At present, GS products are not only used to promote health, but also for their activity as immune regulators in many diseases (Jiang Z. et al, 2017; Shin et al, 2018; Yu X. et al, 2018). GS exert a cytoprotective effect, thereby promoting cell viability on avian influenza H9N2/G1 infection.…”
Section: Anti-infection Effects Of Chmsmentioning
confidence: 99%